2020
DOI: 10.1186/s12864-020-07023-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization and expression profiling of MAPK cascade genes in Salvia miltiorrhiza reveals the function of SmMAPK3 and SmMAPK1 in secondary metabolism

Abstract: Background The contribution of mitogen-activated protein kinase (MAPK) cascades to plant growth and development has been widely studied, but this knowledge has not yet been extended to the medicinal plant Salvia miltiorrhiza, which produces a number of pharmacologically active secondary metabolites. Results In this study, we performed a genome-wide survey and identified six MAPKKK kinases (MAPKKKKs), 83 MAPKK kinases (MAPKKKs), nine MAPK kinases (MAPKKs) and 18 MAPKs in the S. miltiorrhiza genome. Within eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 89 publications
1
11
0
Order By: Relevance
“…The primary factor causing the effects of nanoparticle formulations on two different colon tumors to differ from each other is the origin of the cells. The genome-transcriptome mapping investigation revealed that despite having two separate origins, the CT26 cell has characteristics similar to human primary colorectal cancers in terms of drug resistance mechanisms, gene expression and mutation patterns, and pathways in onco-related genes [ 59 60 ]. Nevertheless, because of their different origins, these cell lines exhibit various genetic and epigenetic changes as well as mutations due to their diverse origins.…”
Section: Resultsmentioning
confidence: 99%
“…The primary factor causing the effects of nanoparticle formulations on two different colon tumors to differ from each other is the origin of the cells. The genome-transcriptome mapping investigation revealed that despite having two separate origins, the CT26 cell has characteristics similar to human primary colorectal cancers in terms of drug resistance mechanisms, gene expression and mutation patterns, and pathways in onco-related genes [ 59 60 ]. Nevertheless, because of their different origins, these cell lines exhibit various genetic and epigenetic changes as well as mutations due to their diverse origins.…”
Section: Resultsmentioning
confidence: 99%
“…Mitogen-activated protein kinase (MAPK) cascades are a prevalent characteristic of eukaryotic cells, involving in plant growth (Zhang et al, 2018), development (Kalapos et al, 2019), stress response (Adachi et al, 2015;He & Meng, 2020), and the biosynthesis of secondary metabolites (De Boer et al, 2011; Devendrakumar, Li & Zhang, 2018;Zheng et al, 2019). In S. miltiorrhiza, eighteen MAPKs have been identified, and two SmMAPKs (SmMAPK1, SmMAPK3) might play a role in tanshinones biosynthesis (Xie et al, 2020). Among the DEGs associated with tanshinones accumulation obtained in this study, there were six MAPK-related genes, and these genes had higher levels of expression in YN samples with high tanshinones content (Table S10), suggesting their possible role in tanshinones accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The kinase-initiated cascades responsible for signal perception and transduction seem to share many similarities, although the specialized metabolites produced by different plants vary significantly. For example, Arabidopsis , S. miltiorrhiza , tobacco, and C. roseus recruit the MAPK cascade to activate the biosynthesis of structurally diverse camalexin, tanshinone, and MIAs (Xie et al 2020 ; Raina et al 2012 ; Xu et al 2008 ; De Boer et al 2011 ; Paul et al 2017 ). Therefore, creating transgenic lines targeting PKs may lead to altered metabolic outcomes in many medicinal plant species.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of MAPKs seem to be conserved in medicinal plants that produce unique specialized metabolites. In Salvia miltiorrhiza , MAPK seems to be associated with the biosynthesis of tanshinone (Xie et al 2020 ). S. miltiorrhiza is a traditional herb in Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%